Oskar Schlemmer's Kitsch (1922): a contextualisation and translation. Issue 1 (1st January 2021) - Brayshaw, Emily
ABSTRACT: This article contextualises a previously unpublished manuscript on the subject of kitsch written in 1922 by the Bauhaus practitioner Oskar Schlemmer and provides an original annotated translation as an appendix. The article positions Schlemmer's manuscript as a response to debates about the aesthetics of kitsch among his contemporaries in the German and Austrian intelligentsia, including Austrian architect Adolf Loos; Stuttgart-based art historian and member of the Deutscher Werkbund Gustav Pazaurek; the founding member of the Dürerbund, Ferdinand Avenarius; and the avant-garde satirist Frank Wedekind. Schlemmer's unpublished manuscript is also located as part of a broader response to the social upheavals of industrialisation and the First World War, where the concept of kitsch figured centrally in discussions among taste-makers about the progress and purpose of art and design in the new century. While "kitsch" in Germany before 1920 was generally considered to be in poor taste and an expression of bourgeois excess, Schlemmer argues that not all kitsch is bad. Schlemmer's manuscript highlights a shift, following the First World War, in attitudes among the German avant-garde towards what constituted kitsch and the role that it may have had on design inspiration within modernist theatre. Like Pazaurek, who classified different categories of kitsch, Schlemmer, too, identifies a new category of kitsch—"true" kitsch—and states not only that it appears as an expression of the joy found in popular entertainment, such as at circuses and market fairs, but that it is beautiful and as such should be celebrated.